Pengaruh Ekstrak Metanol Biji Mahoni (Swetenia mahagoni Jacq) terhadap Penurunan Glukosa Darah dan Perbaikan Jaringan Pankreas Tikus Hasil Induksi MLD-STZ - Nany Suryani; STIKES Husada Borneo (HB PRESS, 2013)
Cancer is a disease that causes most deaths in this century. In general, cancer can affect Diabetes Mellitus (DM) is a disease with metabolism disorder signed by increasing of glucose blood (hyperglicemia), caused by disorder of insulin secretion and or increasing of insulin resistance. Therapy of Methanolic Swetenia mahagoni Seed Extracts is an alternative treatment for DM. The objective of this research is to prove the effect of extract of Swetenia mahagoni Jacq to decreasing blood glucose content and repair pancreatic tissue damage of rat result Multiple Low Dose-Streptozotocin (MLD-STZ )induced dose of 20 mg/kg weight for 5 days successively. Blood glucose of rat was measured using digital glucometer and categorized as DM if it is >300 mg/dL. This research used 25 wistar strained white rat (Rattus norvegicus). Which were classified into 5 groups, they are one group of negative control, one group of positive control, and three groups of MLD-STZ induced given treatment of Methanolic Swetenia mahagoni Seed Extracts with dose of 100, 250 and 400 mg/kg weight for 7 days. The result showed that treatment of Methanolic Swetenia mahagoni Seed Extracts with dose of 100, 250 and 400 mg/kgBW decreased blood glucose 55,47%; 81,01% and 73,63% successively, and improved damage of pancreas tissue from decreasing in the degree of insulitis (p<0.05). There was a protective effect of methanolic Swetenia mahagoni seed extract to blood glucose and damage of rat pancreas tissue MLD-STZ induced. The terapeutic effect was optimal at dose of 250 mg/kgBW.